Health Monitoring of Volatile Organic Compounds (VOCs) in Changwat Rayong - Srisupap, Wullapa; Raksakom, Hansa; Kongsombatsuk, Marissa; Usadee, Chawalnuch; Paniangtong, Suda (Journal of Health Science of Thailand, 2018)
The purposes of this study were to assess health monitoring of VOCs by examining t,t-Muconic acid levels,benzene metabolite, in urine and to compare the relationship between abnormal hematological findings and t,t-Muconic acid testing results. Data were collected from 402 informed consent subjects in responsible areas of Map Taphut hospital and Ban Chang hospital from April to June 2009. The results of this study showed that most subjects were long-term inhabitants for more than 20 years (55.5%) and stayed at home for more than 12 hours per day (91%), There were 48.2 percent of the subjects who reportedly could perceive bad odor and 51.8 percent of those who smelled nothing. They reported symptoms of headache (29.0%), dizziness (27.7%) and eye itching or pain (19.0%). The mean of t-t muconic acid levels was 22.27, SD 68.42 μg./g. and creatinine in the range of 0- 716 μg./gram and creatinine. Only 14.6 percent of the subjects were positive for t,t-Muconic acid in urine. Abnormal red blood cell morphology was statistically significant to the presence of t,t-Muconic acid in urine (p<0.01). Health care providers, therefore, should form a network and plan for long-term and systematic surveillance.